PEMANFAATAN INSTAGRAM SEBAGAI MEDIA DAKWAH PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Hasyim Iskandar; Nur hidayatullah (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
The purpose of this research includes field research. Research using qualitative methods. The method of collecting research data is by collecting data through a descriptive, qualitative approach, through structural interviews. The results of this study are to show that Instagram's nature for preaching makes a positive impact on its users in everyday life. By utilizing the features that exist in the Instagram application. On the Instagram account @Darussalamblokagung Multimedia Darussalam utilizes six Instagram features, namely uploads, captions, comments, likes, followers, hashtags. Multimedia Darussalm preaching about Dawuh guru, Quotes, Video Messages of Da'wah, Sunnah practices, Yaumul milad, Routines. So Instagram can also be used as a medium for preaching as is done by the Instagram account @Darussalamblokagung.